Pychopathic traits and parenting practices in the prediction of childhood behavioural problems - López-Romero, Laura; Romero, Estrella; Gómez-Fraguela, Xose Antón (Anales de Psicología / Annals of Psychology, 2012)
Dysfunctional parenting practices have been evidenced as one of the most important sources of risk for child and adolescent behavioural problems. On the other hand, during the last decade, psychopathic traits have also been shown as important ingredients in order to identify the most severe and persistent patterns of antisocial behaviours. In this line, this study was developed taking into account data collected from parents and teachers about 192 children (aged 6-11 years); a follow up which take place three years later could collect new data on a subsample of 133 children. This study analyzes to what extent psychopathic traits and parenting practices predict the development of behavioural problems. Moreover, interactions among psychopathic traits and family variables are examined, on the basis of the hypotheses suggested by previous studies about the differential role placed by these factors in the developmental pathways of externalizing problems. Results confirm the existence of interactions between psychopathic traits and parenting practices, leading to a loss of influence of educational practices on behavioural problems in the presence of psychopathic affective-interpersonal traits.